2021
DOI: 10.3390/v13050730
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of MALDI-TOF Mass Spectrometry over Real-Time PCR for SARS-CoV-2 RNA Detection

Abstract: At present, the RT-PCR test remains the gold standard for early diagnosis of SARS-CoV-2. Nevertheless, there is growing evidence demonstrating that this technique may generate false-negative results. Here, we aimed to compare the new mass spectrometry-based assay MassARRAY® SARS-CoV-2 Panel with the RT-PCR diagnostic test approved for clinical use. The study group consisted of 168 suspected patients with symptoms of a respiratory infection. After simultaneous analysis by RT-PCR and mass spectrometry methods, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 16 publications
0
50
0
Order By: Relevance
“…At present with the current COVID-19 pandemic, the need for a rapid diagnosis of SARS-CoV-2 has generated a rapid evolution and optimization of clinical methods, including MALDI–TOF MS. Because the gold standard and main diagnosis tool for SARS-CoV-2, the RT-PCR, is continuously producing false negatives, questions are being raised about whether MS-based technology, such as MassARRAY, which demonstrates superior sensitivity and discrimination of mutations within the viral genome, should overtake it [ 114 , 115 ]. MS-based methods using swab and saliva samples are reporting promising results.…”
Section: Current Challenges: Viral Identification and Antimicrobial Resistancementioning
confidence: 99%
“…At present with the current COVID-19 pandemic, the need for a rapid diagnosis of SARS-CoV-2 has generated a rapid evolution and optimization of clinical methods, including MALDI–TOF MS. Because the gold standard and main diagnosis tool for SARS-CoV-2, the RT-PCR, is continuously producing false negatives, questions are being raised about whether MS-based technology, such as MassARRAY, which demonstrates superior sensitivity and discrimination of mutations within the viral genome, should overtake it [ 114 , 115 ]. MS-based methods using swab and saliva samples are reporting promising results.…”
Section: Current Challenges: Viral Identification and Antimicrobial Resistancementioning
confidence: 99%
“…For SARS-CoV-2, a PCR test that was coupled with MS was also widely used to detect this coronavirus ( Table 8 ) [157] , [158] , [159] , [160] . In a Chinese study [159] , a PCR test coupled with an MS test was used to detect the N and ORF 1ab genes of SARS-CoV and the detection rate of this assay was noted to be around 75%.…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%
“…The drawback of this study was that the tendency of the assay to cross-react with other pathogens was unexplored and thus, the test specificity was unclear [160] . The test specificity of the PCR-MS-based test was also unspecified in another study [158] , even though the study reported that such test could detect 400 RNA copies in 1 mL. To further compare the sensitivity and specificity of PCR-MS-based tests in detecting SARS-CoV-2 with other diagnostic methods, a study was conducted in Germany and it was shown that PCR-MS-based assay would produce test sensitivity and specificity that was comparable and concordance to qRT-PCR test findings [157] .…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%
“…Hence, there is a growing popularity of all the above high-throughput multiomics methods involving next-generation sequencing for a wellrounded understanding of COVID-19. MS-based methods have been employed in several clinical studies worldwide, some of which are summarized in Table 1, and have also been indicated to be a superior method for COVID-19 screening [41,42]. This review will, therefore, discuss both mass spectrometry and next generation sequencing-based approaches to interrogate COVID-19.…”
Section: Mass Spectrometry In Disease Researchmentioning
confidence: 99%